Variações de energia na atmosfera em um caso de precipitação intensa no município de Maceió/AL - Alves, Juliana Emanuelle da Costa Andrade (Universidade Federal do Rio Grande do Norte, 2017)
The present work describes a synoptic and energetic evolution of the Easterly Wave Disturbance (EWD) that caused an heavy rainfall episode of greater magnitude in the municipality of Maceió, from July 2 to 3, 2013. For an analysis of the case in question, evidence of precipitation data from the meteorological station of the National Institute of Meteorology. In order to visualize an evolution of the atmospheric system, enhanced termal infrared images of the GOES-13 satellite were used. In addition, ERA5 reanalyses with an endorsement of the behavior of meteorological variables and energy variations during the EWD update period, as well as to calculate the convergence of humidity to the affected one. The EWD synoptic was based on the life cycle phases of the meteorological system. For this, images without Grads software were generated for each phase and variable selected. The specific moisture flux was calculated by vertical integration over an area of interest from the surface up to 300 hPa. The assessment of the energy of the atmosphere on the domains of the continent, ocean and continent / ocean developed through vertically integrated digital calculation of energy terms and conversions. The results showed that after the maturation period of the system, between July 2 and 3, a cumulative maximum daily precipitation reached 145.2 mm in the municipality of Maceió, causing mudslides, flooding and spreading of residues. At that time, a satellite image shown in the eastern and more unstable ondulatory district, with cooler cloud top. The variables vorticity and vertical velocity indicated upward movements in the South Atlantic Ocean during the displacement of the disturbance. A divergence allows a view of the convergence nucleus of greater intensity on Maceió, which coincided with the greater convergent flow of specific humidity on the eastern border of the area bounded to the municipality. The displacement of the meteorological system is also represented by the inverted dug through the pressure at the average ...